Intercultural Communication Pattern Of Muslim Tamil Ethnic With Non-Muslim Tamil In Village Of Madras, Medan City - Zahra, Sylva; Abidin, Syahrul (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
In general, Indians in Medan are Punjabi, Tamil, and Kerala and Sikh. In terms of numbers, however, the Tamil ethnic group is more numerous and widespread throughout North Sumatra. Kampung Madras has been inhabited by Tamil Indians for a very long time. Not only do they have a history of labouring during the Dutch colonial period, but they also possess the culture. This investigation employs a qualitative descriptive methodology. In qualitative research, interviews, observations, and the use of documents are the most common methods. The study's findings indicate that the process of intercultural communication between Muslim Tamils and non-Muslim Tamils must also pass through several phases, beginning with the stage of interactive communication patterns. Kampung Madras has its own regional vernacular, though it frequently employs Indonesian. Muslim Tamils, non-Muslim Tamils, and other ethnic groups have no difficulty with this in terms of sociocultural values. Even elderly residents of Kampung Madras claimed to be Indonesian citizens. The intercultural communication process of the Indian Tamil population in Madras Village, Medan City, was not hindered, but rather intertwined with quite high tolerance, both among fellow Muslim Tamils and non-Muslim Tamils. This is reflected in excellent relations and a lack of communication misunderstandings, as language barriers almost never occur. The Tamil community and other ethnicities in Kampung Madras can suppress the purpose of intercultural communication, which is to alleviate feelings of insecurity. This demonstrates that there are no barriers to communication between them.